2018
DOI: 10.1371/journal.pone.0191466
|View full text |Cite
|
Sign up to set email alerts
|

Empirical study of lane-changing behavior on three Chinese freeways

Abstract: Lane-changing (LC) behavior is investigated on Chinese freeways, where the driving circumstances are relatively aggressive. Three data sets were collected from urban expressways and an intercity highway in the form of traffic videos. Different aspects of LC behaviors are analyzed, i.e., the LC rate, motivation, target lane choice and impact on traffic. The results suggest that LC is a transient behavior that randomly occurs with high frequency, which is the main feature of aggressive driving. Several LC patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…observed is not possible. However, the values of the LC rates obtained are quite consistent with those observed in the empirical studies by Knoop et al (2012) and Guo, Wu, and Zhu (2018). Knoop et al (2012) observed a LC rate of 0.2-0.5 veh −1 km −1 on a motorway in the Netherlands.…”
Section: Density Time-series Plots For A12supporting
confidence: 89%
See 1 more Smart Citation
“…observed is not possible. However, the values of the LC rates obtained are quite consistent with those observed in the empirical studies by Knoop et al (2012) and Guo, Wu, and Zhu (2018). Knoop et al (2012) observed a LC rate of 0.2-0.5 veh −1 km −1 on a motorway in the Netherlands.…”
Section: Density Time-series Plots For A12supporting
confidence: 89%
“…But the considered stretch was a homogenous one and the effect of mandatory lane changes (MLC) on the LC rate is not studied. Guo, Wu, and Zhu (2018) observed higher values in their study ranging from 0.3-1.5 veh −1 km −1 . In this study, the considered stretch took into effect the presence of on/off ramps and they attribute the high LC rates to the aggressive lane changing at these locations.…”
Section: Density Time-series Plots For A12mentioning
confidence: 66%
“…Lane change (LC) behavior studies were conducting by many authors among whom is Guo, 2018 analyzed different aspects of LC behaviors, i.e., the LC rate, motivation, target lane choice and impact on traffic. His results suggested that LC is a transient behavior that randomly occurs with high frequency, which is the main feature of aggressive driving.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In China, due to the aggravation of traffic congestion, many roads in many cities entered the period of reconstruction and expansion in recent years [ 30 ]. When driving on the road, driver’s vision is always blocked by the vehicle in front of them, in rare cases, they can look far away [ 31 , 32 ]. In addition, Huang found that in a tunnel, the driver’s fixation position was 0.604–2.557 s in front of the vehicle, and the distribution of fixation point at night was closer to the front of the vehicle than in the day [ 33 ].…”
Section: Introductionmentioning
confidence: 99%